Cybersecurity Capability and Capacity Building for South Africa - (:unkn) unknown (My University, 2018)
Cybersecurity capability and innovation cannot be attained by a single party; researchers, government, private industry and academia should join hands and create public-private partnerships to share their knowledge and create solutions. If South Africa wants to be sufficiently equipped to respond to cyber-threats and to ensure growth in the cybersecurity sector, the country needs to strengthen the pipeline of cyber talent and support the development of a cybersecurity workforce. These requirements provide an opportunity for industry, in collaboration with government and academia, to initiate innovative and exciting approaches to establish cybersecurity and a cybersecurity workforce in South Africa. This paper considers measures for governments, business and academia to alleviate the cyber skills shortage, and pay particular attention to the South African case.
Keywords: African Research